Schemes of eStories for Children with Social Communication Difficulties. (28th July 2020) - Al Ghurair, Noura; Alnaqi, Ghada
Abstract : The current paper presents the development and the evaluation of an Arabic application (app) for electronic stories (eStories) that can be used as an assistive tool in the rehabilitation of children with social communication difficulties. The development process involved engineers and researchers and speech and language pathologists (SLPs) from a rehabilitation hospital, who formulated the design methodology of the Arabic app. This process is critical when designing tools for children with communication difficulties since they have a wide range of differences in their abilities. The evaluation of the app from the standpoint of the SLPs at a local school suggests that the app is easy to use, and the involvement of these SLPs helped in developing a better solution. The results of the usability study on twenty-five students showed positive evaluation with an average score that signifies that the app has above-average usability. This paper highlights the importance of the evaluation process in catering the app for successful user experience.